The Influence of Tunnel Parameters and Graft Inclination Angle on Clinical and Radiological Outcome at Long-term Follow-up after Arthroscopic Anterior Cruciate Ligament Reconstruction - Santhamoorthy, Thatchinamoorthy; Xavier, Anish Anto; Krun, Kaliaperumal; Dubey, Dharamveer Kumar (Revista Brasileira de Ortopedia, 2024)
Objective To study the influence of various tunnel parameters and graft inclination angle (GIA) on the clinical and radiological outcome after anterior cruciate ligament reconstruction (ACLR) at long-term follow-up.Methods In this retrospective study, 80 patients with isolated anterior cruciate ligament (ACL) injury treated by single bundle ACLR using bone patellar tendon bone (BPTB) and hamstring (HT) autografts were evaluated clinically and radiologically at their long-term follow-up. The study population were divided into two groups based on ideal and nonideal tunnel parameters as well as ideal and nonideal GIA. The various tunnel parameters and GIA were interpreted with clinical and radiological outcome at long-term follow-up.Results Eighty patients, 36 (45%) using BPTB and 44 (55%) using HT autografts, were available to complete the study. Patients with ideal coronal tibial tunnel angle (CTTA) and coronal femoral tunnel angle (CFTA) show superior clinical outcome (pivot shift test) than nonideal CTTA and CFTA, which was found to be statistically significant (p-value < 0.038 and 0.024, respectively). Similarly, patients with ideal coronal tibial tunnel position (CTTP) show superior clinical outcome (International Knee Documentation Committee - IKDC objective) over nonideal CTTP (p-value < 0.017). All other tunnel parameters and GIA were not found to have influence on clinical outcome. None of the tunnel parameters have influenced osteoarthritis (OA) change. There was no progression of OA change in the study population at long-term follow-up after ACLR.Conclusion Ideal coronal tunnel parameters produced a better clinical outcome at long-term follow-up after ACLR. There was no progression of OA change at long-term follow-up after isolated ACLR.
Keywords: anterior cruciate ligament reconstruction; knee joint; osteoarthritis